MicroRNA-221-3p Suppresses the Microglia Activation and Seizures by Inhibiting of HIF-1α in Valproic Acid-Resistant Epilepsy - Fu, Meng; Zhu, Yiqing; Zhang, Junqi; Wu, Wei; Sun, Yunxia; Zhang, Xuemei; Tao, Jie; Li, Zhiping (Frontiers in Pharmacology, 2021)
One-third of patients with epilepsy suffer from drug-resistant epilepsy (DRE). Valproic acid (VPA) is a classic anticonvulsant drug, and its resistance is a crucial predictor of DRE, but the pathogenesis remain unknown. Most patients with VPA-resistant epilepsy appear distinct inflammatory response and local hypoxia. Hypoxia-inducible factor (HIF)-1α is an essential effector molecule of hypoxia and inflammation, and may exert therefore a significant effect on the development of VPA-resistant epilepsy. We systematically assess the significance of HIF-1α on children and mice with VPA-resistant epilepsy, and investigated the micro (mi) RNAs that regulate HIF-1α expression. We established models of VPA-sensitive epilepsy and VPA-resistant epilepsy in mice, and confirmed that they had significant differences in epileptic behavior and electroencephalography data. Through proteomics analysis, we identified that HIF-1α was overexpressed in mice with VPA-resistant epilepsy, and regulated the expression of interleukin-1β and tumor necrosis factor-α. Increased expression of HIF-1α led to the increase of microglia and induced their polarization from the M2 phenotype to M1 phenotype, which triggered the release of proinflammatory mediators. Bioinformatics analysis of public databases demonstrated that miR-221-3p was reduced in VPA-resistant epilepsy, and negatively regulated HIF-1α expression. Intervention using miR-221-3p mimics reduced HIF-1α expression markedly and suppressed the activation of microglia and the release of inflammatory mediators, which relieved epileptic seizures of VPA-resistant epilepsy. These observations reveal miR-221-3p/HIF-1α as essential component in pathogenesis of VPA-resistant epilepsy which represent therapeutic antiseizure targets.